DESAIN DAN STABILITAS KAPAL WISATA GALAHERANG MENGGUNAKAN SOFTWARE MAXSURF - Aqilla Ananta; Arfena Deah Lestari; Mochammad Meddy Danial (Riset Sains dan Teknologi Kelautan, 2025)
This study aims to analyze the design and stability of the Galaherang tourist vessel operating on the Kapuas River, Pontianak, using Maxsurf software. The Galaherang is a river-based passenger vessel designed to accommodate approximately 97 passengers and 4 crew members. The analysis includes hull form modeling using Maxsurf Modeler and stability simulation using Maxsurf Stability. The study encompasses hydrostatic calculations, equilibrium analysis, and large angle stability assessment. The results show that the vessel has principal dimensions of LOA 21 m, LWL 17.6 m, beam 5 m, depth 3 m, total height 8 m, and draft 1.61 m. The vessel’s transverse metacentric height (GMt) is 0.957 m under full load conditions. The righting arm (GZ) curve reaches a maximum of 0.523 m at a heeling angle of 45.5°, with an area under the curve of 71.583 m·deg for the 0–30° range. Simulations under dynamic conditions, such as passenger crowding and turning, result in heel angles ranging from 7.5° to 10°, which remain within safe limits. The design complies with the minimum stability criteria set by IMO Resolution A.749(18) Chapter 3 and the BKI standards for passenger vessels, meeting requirements for initial stability, large-angle stability, and longitudinal balance.